Effect of Using Smartphone Media on Reading Interest and Indonesian Language Learning Outcomes of Class IV Students UPT SDN Lambongan No. 7 Selayar Islands - Asdayana Chandrajaya; Munirah Munirah; Muhammad Akhir (Edumaspul: Jurnal Pendidikan, 2022)
Learning Indonesian in elementary school is inseparable from the four language skills namely, listening, speaking, reading, and writing. Interest in reading is an important factor in achieving learning outcomes. If the subject matter is not in accordance with students' reading interests, students will not study well. Technological factors, for example, students are willing to spend hours just playing smartphones so that students forget the time to study. The purpose of this study was to determine the effect of using smartphone media on reading interest and Indonesian language learning outcomes for class IV UPT SDN Lambongan No.7 Selayar Islands. The population is all students at UPT SDN Lambongan No.7 Selayar Islands, namely 107 students. This type of research is an experiment using a quantitative approach. The quasi-experimental design model used is the nonequivalent control group design. The sampling technique uses saturated sampling. The sample in this study was class IVb, totaling 15 people as the control class and class IVa, totaling 15 people as the experimental class. Types of data collection using questionnaires, tests and documentation. Data analysis in this study is the Normality Test and T-Test. In the control class, the results of interest in reading Indonesian for class IV students before using smartphone media , namely with a value of 30 and after using smartphone media , namely with a value of 80. In the experimental class, the results of using smartphone media on student learning outcomes in class IV before the posttest, namely with a value of 62 and after possttest, namely with a value of 100. This value indicates a Minimum Learning Mastery (KBM) of 70 for Indonesian material has been achieved. The results of the t-test for equality of means can be seen = 9.443 from these calculations it can be obtained 9.443 > 2.021 ( > ) and the significance is 0.000 <0.05, it can be said that rejected and accepted can mean that there is an effect of using smartphone media on reading interest and results learning Indonesian. So, it can be concluded that there is an effect of the use of smartphone media on reading interest and Indonesian learning outcomes. So, it can be concluded that the use of smartphone media has an influence on reading interest and Indonesian language learning outcomes for class IV UPT SDN Lambongan No.7 Selayar Islands.